The Influence of Location, Price, Promotion, and Laundry Fragrance on the Decision to Use Laundry Services in Makassar - Arif, Muh.; Alimukti, Bagus Alwi; Ab, Ahmad; Zulkifli, Andi Ade (Media Wisata, 2024)
This study aims to analyze the effect of location, price, promotion, and laundry perfume aroma partially and simultaneously on decisions to use laundry services in Makassar. Data were collected through a survey of 165 laundry customers in Makassar. The analysis technique used is multiple linear regression. The results showed that location and promotion have a positive and significant effect on the decision to use laundry services while price and laundry perfume aroma have a negative and significant effect on the decision to use laundry services. The closer or easier the location of the laundry to the customer's residence, the cheaper the price offered, and the more intensive the promotion carried out, the more likely the customer is to use laundry services. The smell of laundry perfume that does not follow the tastes of laundry consumers will result in a decrease in the decision to use laundry services by consumers. Simultaneously, the variables of location, price, promotion, and laundry perfume aroma have a simultaneous and significant effect on the decision to use laundry services. Based on the results of this study, it is recommended for entrepreneurs or managers of laundry businesses to pay attention to business locations, prices offered, promotions carried out, and the aroma of laundry perfume used to increase the number of laundry customers.